Metal‐Free, Multicomponent Anti‐Markovnikov Hydroarylsulfonylation and Alkoxyarylsulfonylation of Vinyl Arenes. Issue 2 (3rd December 2020) - Das, Pritha; Das, Subhodeep; Varalaxmi, Kasarla; Jana, Ranjan
Abstract: A unified strategy for the hydro‐arylsulfonylation of vinyl arenes has been developed under catalyst, additive‐free conditions at room temperature from the corresponding aryldiazonium salts, DABSO (DABCO ⋅ 2SO2 ), and thiophenol as hydrogen atom transfer (HAT) reagent. Mechanistically, an incipient arylsulfonyl radical is generated from the corresponding aryl diazonium salts and DABSO which undergoes anti‐Markovnikov addition to styrenes followed by hydrogen atom transfer from thiophenol. Interestingly, this multi‐component reaction is highly chemoselective suppressing deleterious thiosulfonylation and thiol‐ene reactions. Tuning the reaction conditions, a four‐component difunctionalization with alkoxy group has been achieved using 1, 4‐dicyanobenzene as an oxidant. Furthermore, base‐promoted elimination to form vinyl sulfone has been also examined. The practicability of this present reaction has been demonstrated by the ex situ generation of sulfur dioxide in an H‐type reaction vessel and subsequent hydro‐ and alkoxyarylsulfonylation in good to moderate yields. The hydroarylsulfonylation reaction is scalable and applied to a metal‐free synthesis of the key intermediate for an anti‐migraine drug Eletriptan. Abstract :